Alterations in the Levels of Ions in Tissues of Freshwater Fish Cirrhinus mrigala Exposed to Deltamethrin - M David, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Alterations in the Levels of Ions in Tissues of Freshwater Fish Cirrhinus mrigala Exposed to Deltamethrin